2020
DOI: 10.1186/s12947-020-00192-4
|View full text |Cite
|
Sign up to set email alerts
|

Left atrial reservoir strain combined with E/E' as a better single measure to predict elevated LV filling pressures in patients with coronary artery disease

Abstract: Background: The 2016 guidelines for left ventricular diastolic dysfunction diagnosis has been simplified from previous versions; however, multiparametric diagnosis approach still exists indeterminate left ventricular diastolic dysfunction category. Left atrial (LA) strain was recently found useful to predict elevated left ventricular (LV) filling pressures noninvasively. This study aimed to (1) analyze the diagnostic value of LA strain for noninvasive assessment of LV filling pressures in patients with stable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 45 publications
3
36
0
1
Order By: Relevance
“…LAS by STE shows a promising, non-invasive approach to predicting changes in LV filling pressure. Recent studies show that LAS at reservoir phase predicts elevated LV end-diastolic pressure in patients with coronary artery disease [ 79 ] and patients with normal LVEF [ 45 ]. Another study that included 76 patients referred for left heart catheterization demonstrated LA reservoir strain to be an independent predictor of LV filling pressure, with a cutoff value of LASr < 20% being optimal to detect elevated LV filling pressure (area under the curve 0.76) [ 47 ].…”
Section: Prognostic Value Of La Deformationmentioning
confidence: 99%
“…LAS by STE shows a promising, non-invasive approach to predicting changes in LV filling pressure. Recent studies show that LAS at reservoir phase predicts elevated LV end-diastolic pressure in patients with coronary artery disease [ 79 ] and patients with normal LVEF [ 45 ]. Another study that included 76 patients referred for left heart catheterization demonstrated LA reservoir strain to be an independent predictor of LV filling pressure, with a cutoff value of LASr < 20% being optimal to detect elevated LV filling pressure (area under the curve 0.76) [ 47 ].…”
Section: Prognostic Value Of La Deformationmentioning
confidence: 99%
“…LA reservoir function represents LA filling by pulmonary vein flow during ventricular systole and demonstrates stiffness of the left atrium, producing higher pressures. For example, LA reservoir strain has previously been correlated with left ventricular filling parameters and negatively correlated with mean pulmonary artery pressure and pulmonary capillary wedge pressure [20,21]. Owing to the pathophysiological link between left-side heart diseases and the development of functional TR, the finding that recurrent TR could be predicted by parameters correlating with LA function can be explained.…”
Section: Discussionmentioning
confidence: 99%
“…LASI [38,39] or LA compliance (the reciprocal of LASI) [7] is useful in predicting elevated LV lling pressures and identifying patients with HFpEF. In our community-based population, LASI was also correlated with plasma NTproBNP and other echocardiographic parameters demonstrating raised left ventricular lling pressures (E', LAVI, TR velocity).…”
Section: Role Of Lasi As a Single Indexmentioning
confidence: 99%